Analysis of the regulatory game of government environmental protection departments on corporate pollution control - Song Shibo (SHS Web of Conferences)
In recent years, China’s rapid economic growth at the same time, promote the construction of ecological civilization, and constantly improve the enterprise pollution control policy, optimize the environmental protection department on the supervision of corporate sewage behavior, and promote the transformation of the country’s ecological civilization and a strong country. However, there are still many enterprises still lack of environmental awareness, in order to maintain their own interests, constantly “drilling” system “loopholes”, do not take the initiative to invest in pollution control, choose to indulge in the problem of sewage disposal, falsification of enterprise data, so as to obtain improper excess earnings, resulting in a serious negative externality. Serious negative externalities. In this regard, this paper will use the game model to analyze the government’s environmental protection department to govern the degree of strictness, improve the enterprise pollution violation emission punishment mechanism, etc., the impact of the change of these parameters will make the enterprise pollution control behavior to improve. The results of the study show that increasing the management system of environmental protection department personnel and enhancing the punishment for corporate pollution violation discharge behavior can effectively reduce the emergence of corporate pollution violation behavior.